Food solidarity economy: evaluating transition community initiatives in Friuli Venezia Giulia region - Lucia Piani; Matteo Carzedda; Nadia Carestiato (Agricultural and Food Economics, 2021)
Abstract Climate change, ecological challenges, and economic and social crises imply paradigmatic and structural innovations. In the effort to drive transition toward sustainability, local communities often take the lead, mobilize support, and organize initiatives based on the principles of solidarity economy. Our study presents a qualitative evaluation and comparison of three local bottom-up initiatives from Friuli Venezia Giulia, a Northern Italian region, each following alternative and unique models of production and consumption of wheat and flour. The reconstruction of the transition paths of the experiences, together with documental analysis and interviews, allowed us to deduce the influence of alternative approaches and subsequent degree of effectiveness in building a community and driving it toward sustainability.